THE STUDY OF ANTI-INFLAMMATORY ACTIVITY OF NEW MEDICINAL FORMS FOR THE TREATMENT OF CARIES OF THE DENTIN - A. L. Golovanenko; I. P. Rudakova; I. V. Alekseeva; E. S. Berezina; V. V. Novikova (Разработка и регистрация лекарственных средств)
Аs a result of a set of scientific and experimental studies, gel and drug films have been developed that provide intensive mineralization of dentin. Previously conducted preclinical studies have studied the specific remineralizing activity and antimicrobial effect, as well as acute toxicity of dosage forms. To determine the anti-inflammatory activity, a model of acute inflammatory edema was used to evaluate the increase in the volume of the inflamed foot of rats, by introducing a phlogogenic agent. Based on the results obtained, it is established that the gel and the drug films have a sufficiently pronounced anti-inflammatory effect.